2014
DOI: 10.7554/elife.05375
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of the small regulatory RNA RydC by the bacterial Hfq protein

Abstract: Bacterial small RNAs (sRNAs) are key elements of regulatory networks that modulate gene expression. The sRNA RydC of Salmonella sp. and Escherichia coli is an example of this class of riboregulators. Like many other sRNAs, RydC bears a ‘seed’ region that recognises specific transcripts through base-pairing, and its activities are facilitated by the RNA chaperone Hfq. The crystal structure of RydC in complex with E. coli Hfq at a 3.48 Å resolution illuminates how the protein interacts with and presents the sRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
129
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(139 citation statements)
references
References 63 publications
(95 reference statements)
10
129
0
Order By: Relevance
“…The CTD has been proposed to stabilize RNA·Hfq complexes via direct interactions with sRNAs (19,36,57) owing to the slightly weaker binding of sRNAs in the absence of the CTD (10, 25), which we have recapitulated (Table 1). However, the data presented in this paper do not support this stabilization model because the CTDs do not increase the affinity of RNA oligomers (A18-FAM and D16-FAM) ( Table 1) and actually decrease the affinity of RNA stem loops (beacon and minRCRB) ( Table 1).…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…The CTD has been proposed to stabilize RNA·Hfq complexes via direct interactions with sRNAs (19,36,57) owing to the slightly weaker binding of sRNAs in the absence of the CTD (10, 25), which we have recapitulated (Table 1). However, the data presented in this paper do not support this stabilization model because the CTDs do not increase the affinity of RNA oligomers (A18-FAM and D16-FAM) ( Table 1) and actually decrease the affinity of RNA stem loops (beacon and minRCRB) ( Table 1).…”
Section: Discussionmentioning
confidence: 49%
“…The CTD is not essential for sRNA recognition, because truncated Hfq variants lacking all or part of the CTD bind sRNAs in vitro and in the cell (10, 23-26, 28, 36). However, partial ordering of the CTDs in a recent structure of Hfq bound to RydC sRNA suggested that the CTDs help recruit sRNAs to Hfq (36).…”
mentioning
confidence: 99%
“…To efficiently facilitate pairing, the target sequence (in mRNA) and the seed sequence (sRNA) should not be bound on Hfq, but instead presented for interaction. This may involve Hfq-induced RNA folding changes (e.g., Henderson et al, 2013), and the arginine patches on the rim could promote the alignment of flexible single-strands of seed and complement (Panja et al, 2013), in line with results from a recent cocrystal structure of RydCeHfq (Dimastrogiovanni et al, 2014). Indeed, Hfq binding sites far away from, ordconverselydoverlapping a seed/target site, are unfavorable (Beisel et al, 2012;Panja & Woodson, 2012;Peng, Soper, et al, 2014).…”
Section: Rna Binding and Promotion Of Srnaemrna Pairingmentioning
confidence: 52%
“…It is interesting to note that a hairpin-less RNA possessing a base-pairing region and a poly(U) tail is able to base pair with a beacon probe RNA in the presence of Hfq in vitro (Panja et al 2013). In addition, a structural analysis demonstrated that the hairpin structure seems to be not involved in interactions with Hfq (Dimastrogiovanni et al 2014). These results suggest that the terminator RNA hairpin plays no role in Hfq binding itself.…”
Section: Discussionmentioning
confidence: 88%